Role of Manufacturing Industries in Nepalese Economy - Gautam, Meera (Management Dynamics, 2018)
Nepal is an agriculture country major labor force is employed, and contributes nearly thirty percent of GDP. Countries have adopted the policy of industrialization and create jobs for the economic active population. This paper discusses and tries to identify the role played by the manufacturing enterprises. Basically share in GDP, employment, value addition and gender participation. A simple average, straight line growth trend and percentiles are used for the role measurement. The source of data is mainly censuses on manufacturing enterprises conducted in Nepal since first one from1991 to last one in 2012 and Economic Survey. Analysis of the data indicates that the total number of operating establishments is declining, in the same way the total number of employees is also declining. The highest percentages of female workers are engaged as operative workers in all the CMEs. It is realized that whatever the status measured may help to the policy makers or researchers to correlate and analyze further. It is recommended the need of further information is needed on market opportunities and challenges in the past and present, investment and export potential and bottlenecks. This would be useful to entrepreneurs and policy makers alike.